You must set forth at dawn a memoir - Soyinka, Wole. (New York Random House, 2006)
The first African to receive the Nobel Prize in Literature, as well as a political activist of prodigious energies, Wole Soyinka now follows his modern classic "Ake: The Years of Childhood" with an equally important chronicle of his turbulent life as an adult in (and in exile from) his beloved, beleaguered homeland. In the tough, humane, and lyrical language that has typified his plays and novels, Soyinka captures the indomitable spirit of Nigeria itself by bringing to life the friends and family who bolstered and inspired him, and by describing the pioneering theatre works that defied censure and tradition. Soyinka not only recounts his exile and the terrible reign of General Sani Abacha, but shares vivid memories and playful anecdotes - including his improbable friendship with a prominent Nigerian businessman and the time he smuggled a frozen wildcat into America so that his students could experience a proper Nigerian barbecue. More than a major figure in the world of literature, Wole Soyinka is a courageous voice for human rights, democracy, and freedom." You Must Set Forth at Dawn" is an intimate chronicle of his thrilling public life, a meditation on justice and tyranny, and a mesmerising testament to a ravaged yet hopeful land.
Keywords: Soyinka, Wole